Pro-Insting (Financial Inclusion Program to Prevent Stunting) for Economic Empowerment & Movement to Accelerate Financial Inclusion for Women - Yulianti M Manan; Dedik Kurniawan (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction: One of the main themes of the Sustainable Development Goals (SDGs) is reducing poverty, hunger, and increasing inclusive economic access. The SDGs focus on indicators of human resource development, particularly those related to women and children. The results of the third National Financial Literacy Survey (SNLIK) conducted by the Financial Services Authority (OJK) in 2019 showed that the financial literacy index was 38.03% and the financial inclusion index was 76.19%. Further analysis of statistical data shows that there is a disparity in access to utilities and financial literacy between women, which tends to be lower compared to men. In line with this data, the prevalence of malnutrition cases with stunting (failure to grow linearly) is 30.8%, and there are also high rates of toddlers with malnutrition, at 17%. This data shows that Indonesia's current and future generations need serious attention, as well as integral and holistic efforts, to achieve prosperous economic justice and complete health. This study conceptualizes social innovation based on an elaborative process of two vital domains: access to financial inclusion and access to health with a dependency on the family economy, through the Pro-Insting movement (Financial Inclusion Program to Prevent Stunting). Purpose: The purpose of this study is to analyze and design an integrative innovation based on the health-economy movement by increasing access to financial inclusion and becoming an alternative role model for economic and health development businesses for women, especially mothers of children under five, in strategies to increase access to financial inclusion and reduce the prevalence of stunting. Methodology: This study uses a descriptive research design with discussion construction based on a community empowerment-based convergence innovation strategy, implemented using a social enterprise start-up model. The goal of the study is to research and develop sustainable innovation designs that have affectional value in increasing financial inclusion and reducing stunting prevalence rates. The design model for this research is the Pro-Insting roadmap, which refers to the Logical Framework Programming (LFP) protocol. Findings: Pro-Instingis a model that combines elements of social enterprise and aims to bring together two intersecting aspects.